Interpretation of Tuan Guru of Indonesian Ulema Council (MUI)-West Lombok on Religious Moderation Verses - Syamsu Syauqani; Zulyadain Zulyadain (Universitas Islam Negeri (UIN) Salatiga, 2023)
This study discusses one issue, namely the interpretation of the gurus of Majlis Ulama' Indonesia on the verses of religious moderation from the aspect of faith in the Qur'an. This study is a qualitative study. The data of this study is obtained through two sources. First, primary data from in-depth interview techniques to the master teachers who are members of the West Lombok Indonesian Ulema Council community. Second, secondary data obtained through documentation, namely data collection in the form of scientific books and scientific journals. The analysis approach used is content analysis. In this case, researchers analyzed the results of interviews and available documents, resulting in themes. This study found that the verses that show moderation in the Qur'an from the perspective of creed can be categorised into four: first, faith and disbelief as a private matter; second, guidance and hidayah only belong to Allah SWT; third, differences and diversity of beliefs as the will (irādah) of Allah; and fourth, the Prophet was sent as a bearer of good news. The informants emphasised their interpretations from an Islamic da'wah perspective. This study contributes to promoting a moderate understanding of Islamic teachings, maintaining interfaith harmony, and building a harmonious and tolerant society.